Circular Economy in Wastewater Management—The Potential of Source-Separating Sanitation in Rural and Peri-Urban Areas of Northern Finland and Sweden - Lehtoranta, Suvi; Laukka, Vuokko; Vidal, Brenda; Heiderscheidt, Elisangela; Postila, Heini; Nilivaara, Ritva; Herrmann, Inga (Frontiers in Environmental Science, 2022)
Current practices in wastewater management lead to inefficient recovery and reuse of nutrients and can result in environmental problems. Source separation systems have been shown to be an efficient way of recovering nutrients and energy from wastewaters, both in rural and urban context. Studies on nutrient recovery potential and life cycle impacts of source separation systems are mainly limited to small systems (for example a few households) while the impacts of upscaling source separation to a regional level have hardly been studied, especially in sparsely populated areas where the cost of the connection to a main treatment plant is higher. This study examines the regional nutrient balance of two source separation scenarios – black water separation and urine diversion – and compares them to the existing conventional wastewater system. The analysis comprises three sparsely populated regions of northern Finland and Sweden, including rural, peri-urban and urban areas. In addition, climate impacts are assessed based on existing life cycle assessment (LCA) studies. According to the results, by source separation it is possible to achieve a significant increase in the recovery rate of phosphorus (41-81%) and nitrogen (689-864%) compared to the conventional system. Depending on the region up to 65% of the mineral phosphorus and 60% of mineral nitrogen fertilisers could be theoretically replaced. Furthermore, the climate and eutrophication impacts would decrease with the implementation of such systems, but an increase in acidification may occur. However, even if the benefits of source separation systems are undisputed in terms of nutrient recovery, the implementation of such systems would to a large extent require an entire system change of the wastewater treatment sector and a wide paradigm change towards a circular economy.